2016
DOI: 10.1021/acs.jpcb.6b04738
|View full text |Cite
|
Sign up to set email alerts
|

Cosolvent and Crowding Effects on the Temperature and Pressure Dependent Conformational Dynamics and Stability of Globular Actin

Abstract: Actin can be found in nearly all eukaryotic cells and is responsible for many different cellular functions. The polymerization process of actin has been found to be among the most pressure sensitive processes in vivo. In this study, we explored the effects of chaotropic and kosmotropic cosolvents, such as urea and the compatible osmolyte trimethylamine-N-oxide (TMAO), and, to mimic a more cell-like environment, crowding agents on the pressure and temperature stability of globular actin (G-actin). The temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…A sample of pioneering works in the field are. [86][87][88][89][90] The central message of these studies is that the role of the steric crowding does not significantly affect the folding. However, when globular proteins replace crowding agents, the behaviour of the system becomes difficult to explain because of the influence of protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A sample of pioneering works in the field are. [86][87][88][89][90] The central message of these studies is that the role of the steric crowding does not significantly affect the folding. However, when globular proteins replace crowding agents, the behaviour of the system becomes difficult to explain because of the influence of protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…[119,120,149,[153][154][155][156] So far,o smolytes have been observed to increase the p m values of proteins and nucleic acids, whereas urea diminishes the pressure stability in terms of p m . [120,[154][155][156] In contrast, as the cosolvents also modulate the melting temperatureo fb iomolecules, reviewing the effect on DV u needs particularc aution owing to its temperature dependence. Generally, DV u can be obtained from PPC measurements or spectroscopic approaches.…”
Section: Pressure Perturbationmentioning
confidence: 99%
“…The behavior of TMAO and urea in the vicinity of a protein was reported not to change much with pressure (from 1 to 5000 bar) and temperature (from 280 to 330 K) . High‐pressure spectroscopic approaches and pressure perturbation calorimetric (PPC) measurements revealed that both factors, the unfolding pressure ( p m ) and the volume change upon unfolding (Δ V u ), are significantly modulated . So far, osmolytes have been observed to increase the p m values of proteins and nucleic acids, whereas urea diminishes the pressure stability in terms of p m .…”
Section: Cosolvent Effects On the Folding Equilibrium Of Proteins Anmentioning
confidence: 99%
See 1 more Smart Citation
“…[43] Another important-yet largely unexplored-stressf actor for life's function is high hydrostatic pressure (HHP). [49][50][51][52][53][54][55][56] Al arge fraction (> 60 %) of organismsi nt he global biosphere is thriving at ad epth in excess of 1000 ma nd, therefore, exposed to pressures of 100 bar and more;a nd pressure reaches the 1kbar level at the sea floori nt he Marianat rench.H ence, HHP studies on biomolecular systems are ap rerequisite for understanding life in the deep sea, an environment whichi ss ignificant also as the potentialb irth place of life on Earth. [57,58] Further,a sathermodynamic variable, pressure can be used to perturb the intermoleculari nteraction potential between proteins and thus serve as an important physical probe for mapping their conformational landscape and phase behavior.I na ccordancew ith Le Châtelier's principle, application of increasing pressure favors states with lower partial molar volumes, hence pressure can be employed to redistribute the populations of conformational substrates by virtue of their different volumes.…”
Section: Liquid-liquid Phase Separation In Biology and Biotechnologymentioning
confidence: 99%